2008
DOI: 10.1186/cc6887
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcomes from the administration of progesterone for patients with acute severe traumatic brain injury: a randomized controlled trial

Abstract: Background Severe traumatic brain injury (TBI) has been increasing with greater incidence of injuries from traffic or sporting accidents. Although there are a number of animal models of TBI using progesterone for head injury, the effects of progesterone on neurologic outcome of acute TBI patients remain unclear. The aim of the present clinical study was to assess the longer-term efficacy of progesterone on the improvement in neurologic outcome of patients with acute severe TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
306
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(322 citation statements)
references
References 31 publications
10
306
1
5
Order By: Relevance
“…Patients receiving progesterone had a lower 30-day mortality compared to those receiving placebo treatment (Wright et al, 2005). In a second study of 159 severe TBI patients, progesterone administered at 1.0 mg/kg via intramuscular injection and then repeated every 12 h for 5 consecutive days had lower mortality and a more favorable outcome at 3 and 6 months follow-up time points (Xiao et al, 2008).…”
Section: T He Centers For Disease Control and Preventionmentioning
confidence: 92%
“…Patients receiving progesterone had a lower 30-day mortality compared to those receiving placebo treatment (Wright et al, 2005). In a second study of 159 severe TBI patients, progesterone administered at 1.0 mg/kg via intramuscular injection and then repeated every 12 h for 5 consecutive days had lower mortality and a more favorable outcome at 3 and 6 months follow-up time points (Xiao et al, 2008).…”
Section: T He Centers For Disease Control and Preventionmentioning
confidence: 92%
“…The HIT III study targeted a subgroup of the overall population, which only included patients with traumatic subarachnoid hemorrhage. The progesterone study reported by Xiao et al 10 concerned a single-center study. The CRASH trials represented the only "mega trial" conducted in the field of TBI.…”
Section: Clinical Trials In Tbi: Past Experiencementioning
confidence: 99%
“…This is important, for example, because of various trials conducted in mainland China that have shown beneficial effects of decompressive craniectomy, hypothermia, and progesterone. 10,[12][13][14][15] These were all well-designed, high-quality studies. However, it is conceivable that differences may exist in referral policies, potential for selection bias, access to health care, acute and post-acute treatments, and outcome.…”
Section: Clinical Trials In Tbi: Past Experiencementioning
confidence: 99%
“…75 In another clinical study in 159 patients with acute severe TBI (initial GCS Ͻ 8), treatment with progesterone significantly improved neurological outcome at 6 months. 76 A phase III clinical study with progesterone in TBI patients is under way (http://www.Clinicaltrials.gov Identifier: NCT00822900).…”
Section: Clinical Studiesmentioning
confidence: 99%